Poetic Words in the Artistic Text - Axmatovich, Shukurov Axat (European Journal of Life Safety and Stability (2660-9630), 2021)
In terms of use in Uzbek poetic epics on historical themes, poetic, biblical words are productive, they mainly express portable meanings, enrich the poetic content, as well as serve in the creation of a number of poetic arts. The article discusses the use of poetic words in poetic epics on a historical theme, and these words increase the expressive capacity of the literary text.